2021
DOI: 10.1002/ppul.25746
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin airway cast obstruction: Experience, classification, and treatment guideline from Denver

Abstract: Background and Objectives Plastic bronchitis (PB) is a condition characterized by the formation of thick airway casts leading to acute and often life‐threatening airway obstruction. PB occurs mainly in pediatric patients with congenital heart disease (CHO) who have undergone staged surgical palliation (Glenn, Fontan), but can also occur after chemical inhalation, H1N1, severe COVID‐19, sickle cell disease, severe asthma, and other diseases. Mortality risk from PB can be up to 40%–60%, and no treatment guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…), congenital heart disease (CHD), and acute chest syndrome associated with sickle cell disease. 10 , 11 The presented case had no history of recurrent wheezing or atopy and did not respond to the asthma treatment. All these disorders and diseases including asthma were excluded with a detailed examination of the patient.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…), congenital heart disease (CHD), and acute chest syndrome associated with sickle cell disease. 10 , 11 The presented case had no history of recurrent wheezing or atopy and did not respond to the asthma treatment. All these disorders and diseases including asthma were excluded with a detailed examination of the patient.…”
Section: Discussionmentioning
confidence: 88%
“…Fibrinolytic agents and anticoagulants (tPA, unfractionated heparin, and urokinase), dornase alpha against cellular DNA and NAC as mucolytic can be administered by nebulization or intraoperatively through bronchoscope. 5 , 11 Systemic steroids to decrease secretions and anti-inflammatory activity and bronchodilators to assist in airway clearance and to reduce bronchospasm can be given. 5 , 12 Hypertonic saline with chest physiotherapy can be employed in airway clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Liptzin et al [ 40 ] suggested a classification scheme based on the presence (Class II) or absence (Class I) of fibrin, which appeared to be helpful in treatment guiding. In the case of Class I PB, where there is an absence of fibrin, treatment should focus on mucolytics and other accessory measures based on cast pathology for bacteria and inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, PB occurs in congenital heart disease patients who have undergone surgical palliation. Liptzin et al 26 described 11 patients with PB due to congenital heart disease and proposed a novel classification scheme to describe composition of airway casts based on the presence of fibrin and inflammation. Treatment suggestions provided are based on cast characterization.…”
Section: Children's Interstitial and Diffuse Lung Diseasementioning
confidence: 99%